Simultaneous carbonization, activation, and magnetization for producing tea waste biochar and its application in tetracycline removal from the aquatic environment. Issue 4 (August 2021) - Li, Bin; Zhang, Yin; Xu, Jin; Xie, Zhengxin; Tang, Jun; Li, Xuede; Fan, Shisuo
Abstract: Facile modification of biochar to greatly improve its properties and then promoting its potential application is still a challenge. In this study, magnetic porous tea waste biochar (MKHBC) was produced first by hydrothermal pretreatment, impregnation with FeCl3 ·6H2 O and KHCO3, and then pyrolysis at 700 °C to realize simultaneous carbonization, activation, and magnetization. Pristine biochar (HBC) was also prepared as a control. Biochars were characterized by SEM, TEM, XRD, Raman, BET, FTIR, XPS, and elemental analysis. The results showed that MKHBC had a surface area of 1035.11 m 2 g −1, a total pore volume of 0.583 cm 3 g −1, and a micropore volume of 0.344 cm 3 g −1 . More mesoporous structure was present in MKHBC. γ-Fe2 O3 and Fe 0, which determined the magnetic property of MKHBC, were observed in it. The saturated magnetization of MKHBC was 7.28 emu g −1, suggesting that rapid separation of adsorbent can be achieved by an external magnet. Carbon-, nitrogen-, and oxygen-containing groups in biochar significantly changed after modification. Langmuir isotherm and Elovich kinetic model fitted well with the adsorption process of tetracycline (TC) on biochar. The maximum adsorption capacity of TC on MKHBC reached 236.93 mg g −1, which was 14-fold than that of HBC (16.71 mg g −1 ). MKHBC could effectively remove TC in a wide pH range and in the presence of co-existing ions. The dominant mechanisms of TC removal on MKHBC were pore filling and π-π interaction, followed by surface complexation, and H bonding. Therefore, MKHBC has the potential to act as an adsorbent for TC removal from the aquatic environment. Graphical Abstract: ga1 Highlights: A magnetic porous biochar (MKHBC) was produced by simultaneous carbonization, activation, and magnetization. MKHBC had a surface area of 1035.11 m 2 g −1 and a total pore volume of 0.583 cm 3 g −1 . The present of γ-Fe2 O3 and Fe 0 resulted in the magnetic property of MKHBC. The maximum adsorption capacity of TC on MKHBC reached 236.93 mg g −1 . The dominant mechanisms were pore filling and π-π interaction, followed by surface complexation, and H bonding.